Overview of serum glutamic pyruvic transaminase and serum glutamic oxaloacetic transaminase levels in covid-19 patients - Sunaidi, Yanti; Thaslifa; Fitriana; Alwiyah B, Siti (Jurnal Kedokteran Universitas Palangka Raya, 2023)
Covid-19 is an infectious disease that infects the respiratory tract, causing multi-organ damage. Serum Glutamic Pyruvic Transaminase (SGPT) and Serum Glutamic Oxaloacetic Transaminase (SGOT) are enzymes produced in the liver whose presence in the blood is a sign of impaired liver function. One of the damage parameters that can be caused by Covid-19 is an increase in SGPT and SGOT levels. The purpose of this study was to determine the description of SGPT and SGOT levels in Covid-19 patients. This study used observational research with a cross-sectional approach. The results showed that from 100 subjects, SGPT and SGOT levels were increased  13 (13%) subjects, which occurred more in the male sex group as many as 9 (9%) subjects, the age group 46-76 years as many as 12 (12%) subjects and the group with comorbid diseases were 9 (9%) subjects. The conclusion of this study, there was more increase in SGPT and SGOT levels in Covid-19 strains with the category of male sex, age 46-76 years, and having comorbid diseases.